The learning of the wheatstone bridge as a continuous current resistance meter - Barba Maggi, Diego Guillermo (mktDESCUBRE, 2017)
The article describes the process of learning from the theoretical foundation and its relation to practical application Wheatstone bridge as a resistance meter supplied with direct current circuit during the semester from August to November 2014, in the Faculty of Engineering of the University of Buenos Aires. The purpose of the research is to identify, build and simulate the variables and characteristics present in a Wheatstone bridge and applied experimentally to find the ideality of the system through the variation of the resistance of the circuit, the same task was performed with two different voltages to calculate the error to the imprecision in seeking equilibrium condition from Kirchhoff’s laws.The equation relating the current flowing through the galvanometer with the voltage drop circuit resistance and the internal resistance was found galvanometer. The importance of identification, treatment and processing of variables involved in the structure of the Wheatstone bridge and implementation in the training of future professionals in the area of engineering and related sciences evidence validating their results with computer simulations, for effect through SOLVER EXCEL and MICROSOFT MATHEMATICS.